The relationship between subjective sleep disturbance and attenuated psychotic symptoms after accounting for anxiety and depressive symptoms - Formica, Melanie J. C.; Fuller-Tyszkiewicz, M.; Hickie, I.; Olive, L.; Wood, S. J.; Purcell, R.; Yung, A. R.; Phillips, L. J.; Nelson, B.; Pantelis, C.; McGorry, P. D.; Hartmann, Jessica A. (Schizophrenia research, 2023)
Background and hypotheses - Sleep disturbances are increasingly recognized as cooccurring with psychotic symptoms. The potential importance of this relationship is complicated when considering the effects of anxiety and depressive symptoms which commonly present in early-stage illness states. This study aimed to investigate the relationship between self-reported sleep disturbance on the development of attenuated psychotic symptoms (APS) cross-sectionally and longitudinally while adjusting for roles of anxiety and depressive symptoms. - Design - Eight-hundred and two help-seeking young people aged 12 to 25 years who engaged with our Australian early intervention services were included in the study (the “Transitions” cohort). Cross sectional mediation and cross-lagged longitudinal (12-month) mediation models were developed with outcomes being different APS domains. - Results - Only baseline excessive daytime sleepiness predicted later APS when accounting for previous APS, anxiety and depressive symptomatology. Cross sectionally, self-reported sleep disturbance showed both direct and indirect predictive relationships with all APS domains. Partial mediation through anxiety and depression was shown for unusual thought content, perceptual abnormalities, and disorganised speech, while full mediation through depression was shown for non-bizarre ideas. - Conclusions - The specificity of the relationship between self-reported sleep disturbance on APS highlights the potential for different roles in mechanistic models of psychotic symptom expression. This further indicates the need for further experimental research to illuminate potential causal pathways. Future research should continue to use continuous, symptom level approaches across a range of timeframes to more accurately model the complex dynamics present in the sleep-psychosis relationship.